Governor in Indian federalism-II: hiatus between constitutional intents and practices - Pankaj, Ashok (2017)
In this second part of the article, the first part deals with the Constituent Assembly (CA) debates on power, position and role of Governor in the Indian constitution, the profiles of the incumbents of Raj Bhavans, their average tenures and their role as envisaged in the constitution have been examined. It explains that as against the intentions of the constitution-makers, the majority of Governors (52.3 per cent) appointed between 1950 and April 2015 have been from active political backgrounds including former chief ministers who constituted 12.9 per cent. Only 18 per cent of the tenures of Governors have been of full 5-year term and another 8 per cent of between 4 and 5 years. Except for a few who rose above partisan considerations, Governors have often obliged on the political demands of the union government and worst on the ruling party at the centre. This hiatus between constitutional intents and practices has widened since 1967. While there have been many course corrections in Indian federalism in recent years, the role of Governor continues to be largely on uncorrected path, except one major improvement-a judicial check on the misuse of Article 356 following the Bommai judgment. - Reproduced.
Keywords: India - Constitution; Constitutions; Federalism - India; India - Governor; Governors